2015
DOI: 10.14238/pi55.4.2015.11
|View full text |Cite
|
Sign up to set email alerts
|

Risk of nutritional status on diarrhea among under five children

Abstract: Background Diarrhea is still the leading cause of children's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
1
0
1
Order By: Relevance
“…However, four out of six severely undernourished patients require hospitalization for more than seven days. This fact is similar to the results of a research study by Iskandar, Sukardi, & Soenarto (2015) stating that episodes of diarrhea in severely undernourished patients are significantly correlated with their length of stay but do not correlate with the severity and duration of the diarrhea itself. Another study by Bhatnagar, Kumar, Dua, Basu, & Kumar (2019) showed that the length of stay for malnourished children with diarrhea is, on average, three days longer than that for malnourished patients without diarrhea.…”
Section: Discussionsupporting
confidence: 89%
“…However, four out of six severely undernourished patients require hospitalization for more than seven days. This fact is similar to the results of a research study by Iskandar, Sukardi, & Soenarto (2015) stating that episodes of diarrhea in severely undernourished patients are significantly correlated with their length of stay but do not correlate with the severity and duration of the diarrhea itself. Another study by Bhatnagar, Kumar, Dua, Basu, & Kumar (2019) showed that the length of stay for malnourished children with diarrhea is, on average, three days longer than that for malnourished patients without diarrhea.…”
Section: Discussionsupporting
confidence: 89%
“…This was because the supplementary foods may increase the risk of children to expose to various types of disease caused by pathogenic microorganisms derived from water contaminated with disease. The result of this study was in accordance with a study done by Iskandar et al (2015) which stated thatbreast milk has all the elements that fulfill the nutritional needs of infants over a period of about 6 months, unless the mother experienced severe less nutrition or other health problems. Nutritional status was a very important aspect for children, and nutritional status played a role in a child's immunity.…”
Section: The Effect Of Exclusive Breastfeeding On Diarrhea Incidence In Children Under Fivesupporting
confidence: 89%
“…According to Iskandar et al (2015), nutritional status was important for children, and nutritional status played a role in a child's immunity. Malnourished children can cause various diseases, such as diarrhea.…”
Section: The Effect Of Exclusive Breastfeeding On Diarrhea Incidence In Children Under Fivementioning
confidence: 99%
“…Namun, hasil penelitian ini sejalan dengan penelitian Iskandar dkk. 16 bahwa balita yang mengalami diare akut mayoritas oleh status gizi baik (96,7%). Balita yang pada dasarnya memiliki status gizi kurang sangat rentan mengalami infeksi karena protein sebagai salah satu sumber gizi berperan dalam pembentukan sistem imun.…”
Section: Pembahasanunclassified